2020
DOI: 10.1097/mop.0000000000000971
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic trends and characteristics of SARS-CoV-2 infections among children in the United States

Abstract: Purpose of review To review the epidemiological characteristics and clinical features associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections among children in the United States. Recent findings In the United States, the majority of SARS-CoV-2 infections in children have been mild illnesses, with those 5–17 years of age having the highest frequency. Specifically, the incidence of SARS-CoV-2 in children is two times higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 29 publications
1
20
0
3
Order By: Relevance
“…Although we did not see an increase in the overall number of mental health–related ED visits, the observed increase in the proportion of mental health–related ED visits aligns with reported increases in prevalence of mood, anxiety, and eating disorder symptoms in the general population [ [15] , [16] , [17] , [18] ]. Youth have been less affected by medical complications of COVID-19 [ 19 ], and have been less likely to present to the ED for other reasons since the beginning of the pandemic [ 13 ]. This could be owing to youth having fewer opportunities to contract other infections and injuries and could explain the increase in proportion of mental health–related visits without an overall increase in visit numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not see an increase in the overall number of mental health–related ED visits, the observed increase in the proportion of mental health–related ED visits aligns with reported increases in prevalence of mood, anxiety, and eating disorder symptoms in the general population [ [15] , [16] , [17] , [18] ]. Youth have been less affected by medical complications of COVID-19 [ 19 ], and have been less likely to present to the ED for other reasons since the beginning of the pandemic [ 13 ]. This could be owing to youth having fewer opportunities to contract other infections and injuries and could explain the increase in proportion of mental health–related visits without an overall increase in visit numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that younger children between the age of 0–12 years are more likely to be tested positive for SARS-CoV-2, because of the occurrence of the Alpha variant (median 8.6 years (min 0.0 years; max 17.8 years)). An epidemiological review comprising data from March–October 2020 in the United States showed that the SARS-CoV-2 incidence was two times higher in adolescents (12–17 years) than in younger children (5–11 years) [ 24 ]. This period does not include the Alpha lineage with high certainty, even though testing for Alpha had not been established then.…”
Section: Discussionmentioning
confidence: 99%
“…Children of all ages are susceptible to COVID-19 (19). Despite the higher incidence of COVID-19 in older children, infants (<1 year) seem to be the most vulnerable due to a high hospitalization rate (20). The average incubation period for COVID-19 in children is about 6.5 days, which is longer than the 5.4 days reported in adults (21).…”
Section: Epidemiologic Featuresmentioning
confidence: 91%